Immunohistochemical Expression of Cyclooxygenase‐2 (COX‐2) in Feline Endometrial Adenocarcinoma and in Normal and Hyperplastic Endometria. Issue 2 (13th February 2015) - Saraiva, AL; Payan‐Carreira, R; Gärtner, F; Santana, I; Rêma, A; Lourenço, LM; Pires, MA
Contents: Cyclooxygenase‐2 (COX‐2) is overexpressed in several human and animal neoplasms, including the human endometrial carcinoma. It has been suggested as a prognostic marker and a potential therapeutic target. This study aimed to (i) clarify histological aspects of feline endometrial adenocarcinomas (FEA) of the papillary serous type and (ii) characterize COX‐2 immunohistochemical expression in normal, hyperplastic and neoplastic endometrium in this species. Archived paraffin‐embedded tissue samples of 33 FEA, eight cystic endometrial hyperplasias (CEHs) and 21 samples of normal, healthy endometrium in the follicular (FS; n = 10) and luteal (LS; n = 11) stages were evaluated. Histological evaluation of haematoxylin and eosin‐stained sections of the FEA revealed a papillary proliferation of neoplastic cells of serous type, accompanied by clear and multinucleated cells. Other architectural arrangements mainly included solid and tubular growth. Randomly distributed areas of necrosis within the tumours were commonly observed. Invasion of the myometrium, of the serosa and of the vascular and/or lymphatic vessels was not constant features. The mean number of mitoses was higher in FEA compared to non‐neoplastic endometrium. COX‐2 scores were lower in FEA (p   =   0.003) and CEH (p   =   0.05) when compared to normal epithelium (NE). The loss of the membrane apical reinforcement in epithelial cells was observed in FEA samples, which was accompanied by the dislocation of COX‐2 labelling into the cytoplasm and the perinuclear area; in contrast, in epithelial cells in the healthy and hyperplastic endometria, the immunoreaction showed the characteristic pattern of apical membrane reinforcement, suggestive of the membrane polarization. COX‐2 epithelial scores were higher in the FS than in the LS. No differences were found in stromal COX‐2 expression between normal, CEH and FEA groups, but it was higher in the LS than in the FS. In summary, loss of COX‐2 compartmentalization in neoplastic epithelial cells might be one of the molecular events underlying endometrial carcinogenesis.